Searching for interstellar C60+ using a new method for high signal-to-noise HST/STIS spectroscopy - Cordiner, M.A.; Cox, N.L.J.; Lallement, R.; Najarro, F.; Cami, J.; Gull, T.R.; Foing, B.H.; Linnartz, H.; Proffitt, C.R.; Sarre, Peter; Charnley, S.B. (American Astronomical Society, 2017)
Due to recent advances in laboratory spectroscopy, the first optical detection of a very large molecule has been claimed in the diffuse interstellar medium (ISM): ${{\rm{C}}}_{60}^{+}$ (ionized Buckminsterfullerene). Confirming the presence of this molecule would have significant implications regarding the carbon budget and chemical complexity of the ISM. Here we present results from a new method for ultra-high signal-to-noise ratio (S/N) spectroscopy of background stars in the near-infrared (at wavelengths of 0.9–1 μm), using the Hubble Space Telescope (HST) Imaging Spectrograph (STIS) in a previously untested "STIS scan" mode. The use of HST provides the crucial benefit of eliminating the need for error-prone telluric-correction methods in the part of the spectrum where the ${{\rm{C}}}_{60}^{+}$ bands lie and where the terrestrial water vapor contamination is severe. Our STIS spectrum of the heavily reddened B0 supergiant star BD+63 1964 reaches an unprecedented S/N for this instrument (~600–800), allowing the detection of the diffuse interstellar band (DIB) at 9577 Å attributed to ${{\rm{C}}}_{60}^{+}$, as well as new DIBs in the near-IR. Unfortunately, the presence of overlapping stellar lines, and the unexpected weakness of the ${{\rm{C}}}_{60}^{+}$ bands in this sightline, prevents conclusive detection of the weaker ${{\rm{C}}}_{60}^{+}$ bands. A probable correlation between the 9577 Å DIB strength and interstellar radiation field is identified, which suggests that more strongly irradiated interstellar sightlines will provide the optimal targets for future ${{\rm{C}}}_{60}^{+}$ searches.